THE EFFECT OF PCV-13 (Pneumococcus Conjugation Vaccine-13) IMMUNIZATION ON THE INCIDENCE OF ARI IN TODDLERS IN URBAN AND RURAL AREAS OF BANDUNG DISTRICT - Anggraeni, Wini; Kunthi Nugrahaeni, Dyan; E Mauliku , Novie (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: Acute Respiratory Tract Infection (ARI) is an acute infectious disease that affects one or more parts of the respiratory tract, from the nose to the alveoli, including the adnexal tissue such as the sinuses, middle ear cavity, and pleura. According to the WHO, pneumonia contributed to 14% of deaths in toddlers in the world in 2019. The WHO recommends that all countries use the Pneumococcal Conjugate Vaccine (PCV) in routine infant immunization. Objective: This study aims to analyze the effect of Pneumococcus Conjugation Vaccine-13 (PCV-13) Immunization on the incidence of ARI in toddlers in urban and rural areas of Bandung Regency. Method: The study employed a cohort study design. The sample in this study consisted of toddlers aged 1-3 years who were registered at the health center posyandu, with both urban and rural characteristics in Bandung Regency, totaling 240 samples. The dependent variable is the incidence of ARI in toddlers. In contrast, the independent variables are the administration of Pneumococcus Conjugation Vaccine-13 (PCV-13) immunization, gender, age of toddlers, nutritional status, immunization history, parental occupation, maternal knowledge, and maternal education. Univariate data analysis to determine the frequency distribution of variables, bivariate analysis using the Chi-Square test, and multivariate analysis using logistic regression. Results of the study: The results showed a significant relationship between the administration of Pneumococcus Conjugation Vaccine-13 (PCV-13) immunization and the incidence of ARI with a p-value of 0.0001 <0.05 and an RR value of 0.000 <1 in urban areas and a p-value in rural areas is 0.0001 <0.05 with an RR value of 0.167 <1 meaning that the administration of Pneumococcus Conjugation Vaccine-13 (PCV-13) immunization can reduce the incidence of ARI in toddlers in both urban and rural areas. Conclusion: Toddlers who receive complete doses of Pneumococcus Conjugation Vaccine-13 (PCV-13) immunization will be protected from ARI